Transcranial Magnetic Stimulation Measures in the Elderly: Reliability, Smallest Detectable Change and the Potential Influence of Lifestyle Habits - Houde, Francis; Laroche, Sarah; Thivierge, Veronique; Martel, Marylie; Harvey, Marie-Philippe; Daigle, Frederique; Olivares-Marchant, Ailin; Beaulieu, Louis-David; Leonard, Guillaume (Frontiers in Aging Neuroscience, 2018)
Background: Transcranial magnetic stimulation (TMS) is a noninvasive technique that can be used to evaluate cortical function and corticospinal pathway in normal and pathological aging. Yet, the psychometric evaluation of TMS-related measurements is still limited in the aging population. Objectives: The aim of this cross-sectional study was to document the reliability and smallest detectable change of TMS measurements among community-dwelling seniors. A secondary objective was to test if TMS measurements differ between elders based on lifestyle, medical and socio-demographic factors. Methods: Motor evoked potentials (MEPs) elicited by single-pulse TMS were recorded in the first dorsal interosseous (FDI) in 26 elderly individuals (mean age = 70 ± 3.8 years). Resting motor threshold (rMT), MEP amplitudes and cortical silent period (cSP) were measured on 2 separate occasions (1-week interval), and the standard error of the measurement (SEMeas), intraclass correlation coefficient (ICC) and smallest detectable change in an individual (SDCindv) were calculated. Lifestyle, medical and socio-demographic factors were collected using questionnaires. TMS-related outcomes were compared using independent sample t-test based on the presence of chronic health diseases, chronic medication intake, obesity, history of smoking, physical activity levels, gender, and level of education. Results: rMT and cSP measures were the most reliable outcomes, with the lowest SEMeas and highest ICCs, whereas MEP amplitude-related measures were less reliable. SDCindv levels were generally high, even for rMT (7.29 %MSO) and cSP (43.16-50.84 ms) measures. Although not systematically significant, results pointed toward a higher corticospinal excitability in elderly individuals who were regularly active, who had no chronic medical conditions and who did not take any medication. Conclusion: Even though SDCindv levels were relatively high, these results show that rMT and cSP are the most reliable outcomes to investigate age-related changes in the corticomotor system and suggest that the influence of factors such as life habits and medications on TMS measures should be investigated further.